Chemical and electrochemical characterization of Nafion containing silver nanoparticles in a stripe-like distribution. Issue 12 (25th January 2016) - Domènech, B.; Romero, V.; Vázquez, M. I.; Avila, M.; Benavente, J.; Muñoz, M.; Macanás, J.
Abstract : Study of the effect of Ag-NPs stripes in Nafion: evaluation of chemical, electrochemical and mechanical properties. Abstract : The particular chemical structure of Nafion with nanostructured and segregated hydrophilic and hydrophobic domains enables its use as a model structure for the manufacture of polymer–metal nanocomposites. Among such nanocomposites, samples of Nafion-117 containing Ag-NPs of ca. 10 nm prepared by Intermatrix Synthesis exhibited a particular distribution in the form of stripes, a regular pattern that could reveal the real morphology of the polymer. To evaluate the potential application of this engineered material ( e.g. in electrochemical devices), these new nanocomposite membranes were characterized by different techniques: microscopic, surface chemical analysis, mechanical and electrical/electrochemical. X-ray (XRD and XPS) analyses combined with synchrotron experiments (XANES) were used to determine the chemical speciation of Ag in the membrane. Membrane potential and impedance spectroscopy measurements showed that such Ag-NPs did not hinder the diffusive transport of protons in the membrane bulk, moreover, they slightly reduced the electrical resistance in fully hydrated state samples. The mechanical evaluation of the nanocomposite evidenced a reduction of the elastic character when compared with the unmodified Nafion-117 sample.